Non-stationary interest rate differentials and the role of monetary policy - Philipp Matros; Enzo Weber (Osteuropa-Institut Regensburg, 2011)
The present work deals with a frequently detected failure of the uncovered interest rate parity (UIP) - the absence of bivariate cointegration between domestic and foreign interest rates. We explain non-stationarity of the interest differential via central bank reactions to exchange rate variations. Thereby, the exchange rate in levels introduces an additional stochastic trend into the system. Trivariate cointegration between the interest rates and the exchange rate accounts for the missing stationarity property of the interest differential. We apply the concept to the case of Turkey and Europe, where we can validate the theoretical considerations by multivariate time series techniques.
Keywords: E44; F31; C32; 330; Uncovered Interest Rate Parity; Monetary Policy Rules; Cointegration; Vector-Error Correction Model; Zinsparität; Kointegration; Fehlerkorrekturmodell; Wechselkurs; Geldpolitik; Reaktionsfunktion; Theorie; Türkei; Eurozone